Analysis of Accounts Receivable Control at Novotel Karawang Hotel - Rahayu, Kintan; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
The purpose of this study was to analyze the accounts receivable control of Novotel Karawang Hotel in 2020-2022 and assess the effectiveness of the accounts receivable collection process. The analysis method used is descriptive quantitative using the Receivable Turnover (RTO) Ratio, Average Collection Period (ACP) Ratio, Arrears Ratio, and Collection Ratio. RTO analysis shows fluctuations, namely from 9 times in 2020, increasing to 26 times in 2021, then decreasing to 21 times in 2022. This value indicates high effectiveness, exceeding the ratio standard of >3.5. Meanwhile, ACP has increased from 39 days in 2020 to 13 days in 2021, then rose slightly to 16 days in 2022. This receivables collection period is within the effectiveness standard of 12-18 days, indicating an increase in efficiency in receivables collection. The Arrears Ratio also shows a decrease in effectiveness in arrears management, with 35% in 2020, 44% in 2021, and 53% in 2022. The effectiveness level of this ratio ranges from 41%-80%, which indicates less effective.Nonetheless, the management of the collection ratio remains effective, as evidenced by Novotel Karawang hotel's ability to generate revenue from sales. The collection ratio reached 181% in 2020, then dropped to 125% in 2021, and 86% in 2022. All of these values are within the 61%-89% ratio effectiveness level, which is considered effective. Hotel Novotel Karawang needs to continue to improve its accounts receivable management to meet company standards and optimize its processes.